Sustainable insect feed in shrimp aquaculture: Challenges and opportunities in research and practical implementation - Barth, Annalena; Justus Liebig University Giessen (My University, 2026)
Aquaculture is a growing global food production sector that aims to meet the increasing demand for human dietary protein. Crustaceans are an important part of aquaculture, particularly the Pacific white shrimp (PWS; Penaeus vannamei). Shrimp farming often has a large ecological footprint, partly due to the fishmeal content in commercial aquafeed. An opportunity to improve sustainability and move towards a circular economy would be replacing fishmeal in aquafeeds with insects, such as the black soldier fly larvae (BSF; Hermetia illucens), reared on plant by-products. However, limited data is available on the effects of novel plant by-products on the growth performance of BSF larvae and in turn on shrimp. Research into BSF-based feed is in its infancy, and the few existing studies show inconsistent results regarding shrimp growth performance. Although some of these discrepancies can be attributed to the properties of the insect feed used, other unknown factors are probably influencing the results. Therefore, this dissertation aims to assess challenges and opportunities in using insects as a sustainable feed in shrimp aquaculture research and practice. It covers key sustainability concerns, enhances the consistency and reproducibility of feeding trials, and offers a comprehensive view of practical application within the context of a circular economy. This dissertation demonstrates that BSF larvae are a promising, sustainable source of protein for shrimp farming. BSF larvae can efficiently convert plant by-products into high-quality protein. Feeding trials show that replacing up to 50% of fishmeal-based compound feed with BSF larvae achieves excellent feed conversion rates. However, the use of BSF meal in compound feed in industrial aquaculture offers greater potential. Furthermore, compliance with reporting guidelines and transparency will be essential for reproducibility and food safety when using insects as feed in the future. The implementation of circular economy concepts remains largely theoretical and depends on optimised rearing systems, increased inclusion rates, industrial scalability and economic profitability. Even though there are still challenges regarding scalability, regulation and consumer acceptance, BSF-based feed has great potential for commercial shrimp farming.
Keywords: ddc:630; ddc:660; ddc:330